6.
Пошаговое объяснение:
(х^2– х – 12)•√(х - 2) = 0
ОДЗ: х - 2 ≥ 0; х ≥ 2;
х∈[2 ; + ∞).
(х^2– х – 12)•√(х - 2) = 0
х^2– х – 12 = 0
или√(х - 2) = 0;
1) х^2– х – 12 = 0
D = b^2 - 4ac = 1+48=49;
x1 = (1+7)/2 = 4;
x2 = (1-7)/2 = -3, не входит в ОДЗ.
2) √(х-2) = 0
х-2 = 0
х = 2
Корни уравнения - 2 и 4,
их сумма равна
2 + 4 = 6.
внизу
Пошаговое )a^3_27b^3=(a-3b)*(a^2+3ab+9b^2)
2)
3)x^6-y^6=(x^3-y^6)*(x^3+y^3)=(x-y)*(x^2+xy+y*2)*(x+y)*(x^2-xy+y^2)
4)k^6+(pq)^6=(k^2+(pq)^2)*(k^4-k^2*(pq)^2+(pq)^4)=(k^2+p^2q^2)*(k^4-k^2p^2q^2+p^4q^4)
5)(ab)^3+b^3=(ab+b)*(a^2b^2-ab^2+b^2)=b*(a+1)*b^2*(a^2-a+1)=b^3*(a+1)*(a^2-a+1)
6)(x-2)^2-27=(x-2-3)*((x-2)^2+(x-2)*3+9)=(x-5)*(x^2-4x+4+3x-6+9)=(x-5)*(x^2-x+7)
7)8a^3+(a-b)^3=(2a+a-b)*(4a^2-2a*(a-b)+(a-b)^2)=(3a-b)*(4a^2-2a^2+2ab+a^2-2ab+b^2)=(3a-b)*(3a^2+b^2)
8)27x^3-y^3(x-y)^3=(3x-y*(x-y))*(9x^2+3xy*(x-y)+y^2*(x-y)^2)=(3x-xy+y^2)*(9x^2+3x^2y-3xy^2+(y*(x-y))^2)=(3x-xy+y^2)*(9x^2+3x^2y-3xy^2+x^2y^2-2xy^3+y^4)объяснение: